2006
DOI: 10.1016/j.bbamcr.2006.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical characterization of S100A8 and S100A9 in the absence and presence of bivalent cations

Abstract: S100A8 and S100A9 are two proinflammatory molecules belonging to the S100 family of calcium-binding proteins. Common to all S100 proteins S100A8 and S100A9 form non-covalently associated complexes which have been shown to exhibit different functional properties. Besides dimerization, recent research is focused on the importance of higher oligomeric structures of S100 proteins induced by bivalent cations. While S100A8/S100A9-heterodimers are formed in the absence of calcium, tetramerization is strictly calcium-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
170
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 155 publications
(184 citation statements)
references
References 30 publications
11
170
3
Order By: Relevance
“…Calgranulin monomers (calgranulin A and B) show a strong preference to form a calcium-dependent heterodimer called calprotectin and is regarded as the functional relevant form at circulating levels (24). This complex has been suggested as a biomarker for inflammation and of utility in the monitoring of disease activity (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calgranulin monomers (calgranulin A and B) show a strong preference to form a calcium-dependent heterodimer called calprotectin and is regarded as the functional relevant form at circulating levels (24). This complex has been suggested as a biomarker for inflammation and of utility in the monitoring of disease activity (25).…”
Section: Discussionmentioning
confidence: 99%
“…At 20 min, regular insulin (0.03 U/kg; Actrapid, Novo, Hellerup, Denmark) was injected as a bolus. Additional samples were obtained from a contralateral antecubital vein at times 1, 2, 3, 4, 5,6,7,8,10,12,14,16,19,20,22,23,24,25,27,30,40, 50, 60, 70, 80, 90, 100, 120, 140, 160, and 180 min. Samples were rapidly collected via a three-way stopcock connected to the butterfly needle.…”
Section: Insulin Sensitivitymentioning
confidence: 99%
“…Recent studies showed that S100 proteins form tetramers or even higher-order oligomers in a calcium-dependent manner, and that oligomerization is an essential prerequisite for their biological functions (16,17). To further investigate the significance of S100A8/S100A9 in H-Ras -mediated cell invasion/migration, we temporarily depleted intracellular calcium in H-Ras MCF10A cells using BAPTA/AM, an intracellular calcium chelator (18).…”
Section: Role Of Calcium In Invasion Migration and S100a8/a9 Expresmentioning
confidence: 99%
“…MRP8 was expressed in E. coli BL21(DE3) cells and purified as previously described (9,30). Briefly, pET11/20 expression vector containing human or murine MRP8 cDNA was used to transform E. coli BL21(DE3) bacteria.…”
Section: Reagents and Absmentioning
confidence: 99%